Increased circulating osteopontin levels promote primary tumour growth, but do not induce metastasis in melanoma - Saup, Rafael; Nair, Nidhi; Shen, Jingyi; Schmaus, Anja; Thiele, Wilko; Garvalov, Boyan K.; Sleeman, Jonathan P. (Biomedicines, 2023)
Osteopontin (OPN) is a phosphoprotein with diverse functions in various physiological and pathological processes. OPN expression is increased in multiple cancers, and OPN within tumour tissue has been shown to promote key stages of cancer development. OPN levels are also elevated in the circulation of cancer patients, which in some cases has been correlated with enhanced metastatic propensity and poor prognosis. However, the precise impact of circulating OPN (cOPN) on tumour growth and progression remains insufficiently understood. To examine the role of cOPN, we used a melanoma model, in which we stably increased the levels of cOPN through adeno-associated virus-mediated transduction. We found that increased cOPN promoted the growth of primary tumours, but did not significantly alter the spontaneous metastasis of melanoma cells to the lymph nodes or lungs, despite an increase in the expression of multiple factors linked to tumour progression. To assess whether cOPN has a role at later stages of metastasis formation, we employed an experimental metastasis model, but again could not detect any increase in pulmonary metastasis in animals with elevated levels of cOPN. These results demonstrate that increased levels of OPN in the circulation play distinct roles during different stages of melanoma progression.